Effect of D122N mutation in BAK1 on structural integrity of protein complex consisting FLS2, flg22 and BAK1 ectodomain- a molecular dynamics study” - Roy, Arka (Brac University, 2021)
This thesis report is submitted in partial fulfillment of the requirement for the degree of Master of Science in Biotechnology, 2020.